Secretome: clues into pathogen infection and clinical applications - Ranganathan, Shoba (BioMed Central, 2009)
The secretome encompasses the complete set of gene products secreted by a cell. Recent studies on secretome analysis reveal that secretory proteins play an important role in pathogen infection and host-pathogen interactions. Excretory/secretory proteins of pathogens change the host cell environment by suppressing the immune system, to aid the proliferation of infection. Identifying secretory proteins involved in pathogen infection will lead to the discovery of potential drug targets and biomarkers for diagnostic applications.